Updates on HIV Pre-exposure Prophylaxis in Latin America: Available Drugs and Implementation Status - Gonzales-Gavancho, Christian (2025)
Latin America has reported a 9% increase in new HIV infections from 2010 to 2023. Pre-exposure prophylaxis (PrEP) is a crucial biomedical intervention for preventing HIV transmission. Currently, several antiretroviral drugs, in various forms of administration, have demonstrated high efficacy and effectiveness to protect against HIV. Among the oral drugs, we have emtricitabine/te-nofovir and emtricitabine/tenofovir alafenamide, while alternative options include the dapivirine vaginal ring, injectable drugs such as Cabotegravir, and the most recently studied Lenacapavir. Despite their high efficacy and effectiveness, implementing PrEP in Latin America has been challenging throughout the region. Although some countries such as Brazil, Mexico, and Colombia have shown progress in increasing the number of users, there is a significant gap between these countries and others where PrEP access remains limited or non-existent. Barriers such as lack of awareness, inadequate funding, political instability, and outdated policies contribute to disparities in access, leaving many populations at high risk of HIV infection without this preventative measure. Innovative strategies need to be implemented to address and monitor policies that ensure access for all at-risk populations.